Coporate governance and Nigerian bailed-out banks' performance : the indirect effect of performance measurement system and board equity ownership - Aliyu, Nuraddeen Shehu (2016)
Perenntal corporate failures had necessitated a bail-out reform in Nigerian banking sector and also the quest for improving managerial effectiveness especially through performance measurement. Most researches concentrated on direct effect of corporate governance on firm performance despite the calls for indirect path. Recent researches suggested multi-dimensional performance measurement systems (PMS) in mediating corporate governance (CG) and firm performance. Drawing upon the agency theory and the resource dependency theory, this study examines the mediating effect of performance measurement systems and moderating effect of board equity ownership in the relationship between corporate governance and bailed-out banks performance. This study used survey to 467 branches managers of bailed-out banks in Nigeria and data was analyzed using a PLS-SEM. The results indicate that board appointment, board size and female membership on board were positively related to banks performance, with the exception of board independence and audit committee quality. This study also found that all the CG variables were related to PMS and PMS is also related to banks performance. As for mediation, all the CG variables were mediated by PMS except board independence. Furthermore, the results showed that board equity ownership is a full moderator between CG (particularly for board independence and audit committee quality) and banks performance. This study concludes that the good structure of CG play a key role in improving bailed-out banks performance. Besides that the evidence indicated that bailed-out banks should also emphasize on board equity ownership and PMS to improve the effectiveness of their CG which in-turn lead to better performance. This study serves as an input to policy makers and regulators in formulating policies and strategies concerning CG. This study also contributes to the CG and PMS literature as scarce attention given on this issue in prior research.